The Transformative Impact of AI in Education: A Technical Analysis - Narasimha Rao Oruganti (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The impact of artificial intelligence on educational systems is examined in this technical article, which also looks at how widely it is being used in institutions around the world. While addressing important technological infrastructure needs and implementation benefits, the article explores the fundamental elements of AI-driven education, such as learning analytics engines, adaptive learning systems, and customization technologies. It explores the major obstacles to integrating AI in education, with an emphasis on privacy standards, digital fairness issues, and data architecture. The article also examines potential technical paths, focusing on new technologies and methods for system integration. It highlights the benefits and challenges of implementing AI while offering insights into how it is changing traditional educational paradigms through thorough data analysis from several educational institutions around the world.